Epos La Galigo: Studi Relasi Antarbudaya Nusantara dan Cina Sebagai Transformasi Pertukaran Budaya Maritim - Wardania Wahyu; Agussalim Burhanuddin (Lembaga Pengembangan Kinerja Dosen, 2025)
The La Galigo epoch is an important literary work that depicts the deep intercultural relationship between the archipelago and China. The story, which focuses on Sawerigading's adventures, not only presents an epic story but also reflects the significant cultural, economic, and political exchanges in Southeast Asia's maritime region. Since the 7th century, the archipelago has been a vital trade route connecting various cultures, with Chinese traders playing a key role in the flow of goods and knowledge. Through the La Galigo Epos, it can be seen how elements of Chinese culture, including shipping technology, trade practices, and social values, have contributed to the development of the archipelago's cultural identity. This integration not only enriches the local culture, but also expands the social and economic horizons of the community. The relationship between the two cultures is the foundation for emerging social and governmental dynamics, demonstrating the positive impact as well as the challenges faced in complex cultural interactions. This epoch is not just a story, but also a historical document that provides important insights into the development of maritime cultural identity in Southeast Asia. By tracing the intercultural relationships established in the La Galigo Epos, we can understand how these interactions shape the region's cultural diversity and richness, as well as provide valuable lessons for future generations in preserving cultural heritage.